Exploration of Nasal Drug Delivery Approach indicated in Unani System of Medicine - Farah Naaz (Indian Journal of Integrative Medicine, 2023)
Introduction: Unani medicine is a holistic and natural healing system based on the time tested and clinically validated remedies and regimens. These haveevolved into a scientific discipline over the time, particularly in India. Intranasal drug delivery plays a pivotal role in this system, offering rapid and non-invasive drug absorption, making it especially suitable for systemic or central nervous system effects. This approach is highly favoured in the treatment of neurological disorders within Unani medicine, where convulsions are attributed to brain vessel obstructions. Various nasal dosage forms are documented, each serving distinct clinical purposes. Objectives: This review explores nasal drug delivery in Unani medicine, focusing on diverse dosage forms for different clinical conditions. Methods: The study relies on exploring Unani manuscripts, including official and non-official pharmacopoeias. Result: Nasal dosage forms in Unani medicine encompass solid, liquid, and gaseous formulations, each serving specific therapeutic purposes. However, classical texts lack specifics on particle size standards for nasal drug administration. Conclusion: The rapid and non-invasive drug absorption offered by intranasal delivery holds promise, particularly for systemic and central nervous system effects. Unani medicine prioritizes this method for managing neurological disorders, attributing convulsions to obstructions in cerebral blood vessels.